Christianity and the transformation of the book : Origen, Eusebius, and the Library of Caesarea - Grafton, Anthony; Williams, Megan Hale, 1969- (The Belknap Press of Harvard University Press, 2008)
When early Christians began to study the Bible, and to write their own history and that of the Jews whom they claimed to supersede, they used scholarly methods invented by the librarians and literary critics of Hellenistic Alexandria. But Origen and Eusebius, two scholars of late Roman Caesarea, did far more. Both produced new kinds of books, in which parallel columns made possible critical comparisons previously unenvisioned, whether between biblical texts or between national histories. Eusebius went even farther, creating new research tools, new forms of history and polemic, and a new kind of library to support both research and book production. Christianity and the Transformation of the Book combines broad-gauged synthesis and close textual analysis to reconstruct the kinds of books and the ways of organizing scholarly inquiry and collaboration among the Christians of Caesarea, on the coast of Roman Palestine. The book explores the dialectical relationship between intellectual history and the history of the book, even as it expands our understanding of early Christian scholarship. Christianity and the Transformation of the Book attends to the social, religious, intellectual, and institutional contexts within which Origen and Eusebius worked, as well as the details of their scholarly practices--practices that, the authors argue, continued to define major sectors of Christian learning for almost two millennia and are, in many ways, still with us today.